Convergence Effects of Clinical Introductory Practicum on Nursing Students - Cho, Young-Hee; Oh, Yun-Jeong; Park, Hae-Ryoung (International Journal of Psychosocial Rehabilitation, 2020)
Background/Objectives: Clinical nursing practice is very important in the nursing education curriculum. The purpose of this study was to identify the convergence effects of clinical introductory practicum on nursing students. Methods/Statistical analysis: Collected data were analyzed using SPSS / WIN 22.0 program. The general characteristics of the subjects were analyzed using descriptive statistics. T-test and ANOVA were used to analyze, Nursing professionalism, Self-efficacy, Clinical competence by the general characteristics, and sheffe’s test was used for post-hoc test. Differences in the variables pre and post clinical introductory practicum of the subjects were analyzed by paired t-test. The correlations between variables were analyzed by Pearson’s Correlation Coefficient. Findings: This study was conducted pre and post clinical introductory practicum for 3rd grade nursing students. Collected data from 93 students who were voluntarily agreed to participate in the study. Data collection period was from December 20, 2017 to February 10, 2018. Nursing professionalism differed by religion (t=-2.84, p=.006), thinking about nursing at entrance (t=2.45, p=.016), thinking about a job as a nurse (F=3.00, p=.035). Self-efficacy differed by school achievement (t=11.43, p<.001), major satisfaction (F=9.93, p<.001), thinking about nursing at entrance (t=2.19 p=.031). Clinical Competence differed by thinking about nursing at entrance (t=2.66, p=.009),thinking about a job as a nurse (F=8.76, p<.001). After clinical introductory practicum, nursing professionalism (t=5.17, p<.001), self-efficacy (t=3.16, p=.002), and clinical competence (t=.352, p=.001) were increased. Clinical competence was positively correlated with nursing professionalism (r=.636, p<.001)and self- efficacy (r=.423, p<.001). Improvements/Applications: It can be used to help adaptation by connecting the school education and the clinical practicum so that the nursing students can reach the nursing goals well.